Realism versus Utopia. Looking for new analytical perspectives - Belardinelli, Sergio (Governare la paura. Journal of interdisciplinary studies, 2016)
Realism and utopia usually represent antithetic political perspectives. In this essay I argue that these might find some common points by overtaking the secular interpretation they usually place on themselves.